The Prognostic Value of Androgen Receptor Splice Variant 7 in Castration-Resistant Prostate Cancer Treated With Novel Hormonal Therapy or Chemotherapy: A Systematic Review and Meta-analysis - Wang, Zhize; Shen, Haixiang; Ma, Nieying; Li, Qinchen; Mao, Yeqing; Wang, Chaojun; Xie, Liping (Frontiers in Oncology, 2020)
Purpose: This study aimed to evaluate the prognostic role of AR-V7 in terms of prostate-specific antigen (PSA) response, progression-free survival (PFS), and overall survival (OS) in CRPC patients treated with novel hormonal therapy (NHT) (Abiraterone and Enzalutamide) or taxane-based chemotherapy (Docetaxel and Cabazitaxel). Methods: A comprehensive literature search was conducted on PubMed, Embase, and the Web of Science from inception to February 2020. Studies focusing on the prognostic values of AR-V7 in CRPC patients treated with NHT or chemotherapy were included in our meta-analysis. The OS and PFS were analyzed based on Hazard ratios (HRs) and 95% confidence intervals (CIs). Furthermore, Odds ratios (ORs) and 95% CIs were summarized for the AR-V7 conversion after treatment and the PSA response. Results: The AR-V7 positive proportion increased significantly after NHT treatment (OR 2.56, 95 % CI 1.51–4.32, P<0.001), however, it declined after chemotherapy (OR 0.51, 95 % CI 0.28–0.93, P=0.003). AR-V7-positive patients showed a significantly decreased PSA response rate after NHT (OR 0.13, 95 % CI 0.09–0.19, P<0.001) but not statistically significant for chemotherapy (OR 0.63, 95 % CI 0.40-1.01, P=0.06). Notably, PFS (HR 3.56, 95 % CI 2.53–5.01, P<0.001) and OS (HR 4.47, 95 % CI 3.03–6.59, P<0.001) were worse in AR-V7-positive CRPC treated with NHT. Similarly, AR-V7 positivity correlated with poor prognosis after chemotherapy as evidenced by shorter OS (HR 1.98, 95 % CI 1.48-2.66, P<0.001) and a significantly shorter PFS (HR 1.35, 95 % CI 0.97-1.87, P=0.07). Conclusion: NHT treatment increased AR-V7 positive proportion whereas chemotherapy decreased it. Moreover, AR-V7 positivity correlated with lower PSA response, poorer PFS, and OS in CRPC treated with NHT, and shorter OS in patients receiving chemotherapy.